ANALISIS USAHA BUDIDAYA JAMUR TIRAM PUTIH (Pleurotus ostreatus) DI KECAMATAN CURUP TENGAH KABUPATEN REJANG LEBONG - Pramudya, Febri Nur; Cahyadinata, Indra (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
The selection of oyster mushrooms as a commodity for business development in Bengkulu wooden mushroom cultivation because the cultivation of oyster mushrooms is relatively easier and faster than with other types of wood mushrooms. Rejang Lebong district is one of the areas in Bengkulu province of the white oyster mushroom cultivation. Business actors in the region of white oyster mushrooms contained in Rejang Lebong Curup Central District. Besides supported by the availability of raw materials in producing white oyster mushrooms such as sawdust, rice bran, lime, and the other as an additional element of media-making baglog, also supported by the availability of the white oyster mushroom market is big enough. The purpose of this study were: 1) Analyzing of income that be obtained from white oyster mushroom bussines of Curup Tengahsub discrict, rejang lebong discrict. 2)Analyzing of level profer or not profer white oyster mushroom bussines in midlle of curup sub discrict, rejang lebong discrict. 3)Analyzing the value- added that be obtained from the white oyster mushroom processing in curup sub discrict, rejang lebong discrict. The results showed that the income earned in Curup Tengah subdistrict white oyster mushroom cultivation in the amount of Rp. 3.901.470, -/Bulan. The magnitude of the efficiency of 1.88. Break even point dalah prices and production is Rp 13.703, - and 10,8 Kg. The amount of the added value obtained from the processing of white oyster mushrooms and a crispy nugget is equal to 33.49% or RP 19.959,02 and 53,77% or Rp 48.226,02 53.